Associations Between Maternal Mental Health and Well-being and Physical Activity and Sedentary Behavior in Children. Issue 6 (July 2017) - Maher, Jaclyn P.; Ra, Chaelin; O'Connor, Sydney G.; Belcher, Britni R.; Leventhal, Adam; Margolin, Gayla; Dunton, Genevieve F.
ABSTRACT: Objective: This study assessed whether aspects of maternal mental health and well-being were associated with objective monitor-based measures of child's physical activity (PA) and sedentary behavior (SB) and the extent to which household structure (i.e., single- vs multigenerational/dual-parent) and maternal employment (i.e., full-time vs not full-time) moderated those associations. Methods: Dyads (N = 191) of mothers and their 8- to 12-year-old children participated in the baseline wave of the Mother's and Their Children's Health study. Mothers (Mage = 40.9 yr [SD = 6.1]; 49% Hispanic) completed a battery of questionnaires to assess maternal mental health and well-being (i.e., self-esteem, life satisfaction, depressive symptoms, anxiety, perceived stress, parenting stress, financial stress, and life events stress). Children (Mage = 9.6 yr [SD = 0.9]; 54% Hispanic; 51% girls) wore an accelerometer across 1 week during waking hours to objectively measure moderate-to-vigorous PA (MVPA) and SB. Results: In single-parent families (n = 47), but not multigenerational/dual-parent families, mothers' parenting stress was negatively associated with child's MVPA (β = −.34, p = .02). In corrected analyses, all other aspects of maternal mental health and well-being were not related to children's activity patterns. Conclusion: Parenting stress was the only maternal mental health variable associated with objective monitor-based measures of child's PA after adjusting for multiple comparisons. Results indicated weaker associations between maternal mental health and well-being and child's MVPA and SB than previously identified using subjective measures of behavior. Study findings support the need to use objective measurements of child's activity patterns to minimize potential confounding because of maternal report in evaluating child's PA and SB.